PROSES PENGEMBANGAN KREATIVITAS SISWA MELALUI EKSTRAKURIKULER ROBOTIC DI SD YPWKS II - Rahmani, Anggi; Yandari, Indhira Asih Vivi; Firdaus, Firdaus; Rahman, Patra Aghtiar; Fajrudin, Lili (Journal of Professional Elementary Education, 2025)
This research aims to describe the process of developing student creativity through robotics extracurriculars. This research was carried out at one of the schools in Cilegon Regency/City, namely at SD YPWKS II. YPWKS II Elementary School. This research uses a qualitative approach and the method used is the descriptive method. [A1] The data collection techniques used were interviews, observation and documentation. By triangulating the sources of school principals, extracurricular teachers and students. The results of this research indicate that the purpose of robotics extracurricular activities is to provide facilities for interests and talents that suit students' needs and provide opportunities for students to hone their skills in the field of robotics. In the application of robotics extracurricular activities, it is usually carried out starting from opening activities, core activities and closing activities. In accordance with the data obtained by researchers, student creativity after the implementation of robotic extracurricular activities at YPWKS II Elementary School, it can be concluded that there are several students who have fulfilled several aspects of creativity.[A2]  namely the fluency aspect where students can produce ideas, flexibility students can think from different points of view and find solutions, originality students can produce unique ideas, and elaboration students can develop and expand existing ideas.